Effect of nanoparticles and hydrogen on combustion performance and exhaust emission of corn blended biodiesel in compression ignition engine with advanced timing. (24th January 2020) - Manigandan, S.; Ponnusamy, Vinoth Kumar; Devi, P.Booma; Oke, Sunday Ayoola; Sohret, Yasin; Venkatesh, S.; Vimal, M.Rakesh; Gunasekar, P.
Abstract: In this study, we have evaluated the influence of Zinc oxide and Titanium dioxide nanoparticles addition in hydrogen-corn blended biodiesel combustion performance and exhaust emission using a dual direct-injection compression-ignition engine. 5% of Zinc oxide and Titanium dioxide were mixed with corn-vegetable oil methyl ester under ultrasonication. Results revealed that the addition of nanoparticles improved the Brake power by 22% (Titanium dioxide) and 4% (Zinc oxide). Consequently, 18% and 15% reduction in brake specific fuel consumption indeed at 50% load compared to neat diesel. Furthermore, the addition of nanoparticles also resulted in a reduction of emission values of 37% and 26% in hydrocarbon, 26% and 36% for carbon monoxide, 19% and 15% in nitrogen oxide and followed by 13% and 8% of smoke opacity. Therefore, the results proved that hydrogen-corn biodiesel blended with nanoparticles additive reports a positive effect on compression-ignition diesel engines without major modifications in engine. Highlights: Dual fuelled hydrogen powered diesel engine studied with nano additives. Corn-hydrogen blends can be used without modifications to engine. BP and BTE is improved upon addition of hydrogen. Emission of CO, HC, NOx and smoke opacity are less for all blends. TiO2 nanoparticles performs superior than ZnO.